P04.59 Modeling the safety of topical agents for skin toxicity associated with tumor treating fields therapy in glioblastoma. (19th September 2018) - Lacouture, M; Hershkovich, H; Giladi, M; Blat, R; Bomzon, Z; Kirson, E; Weinberg, U; Palti, Y
Abstract: Background: Tumor Treating Fields are low intensity, intermediate frequency, alternating electric fields that are approved for the treatment of patients with glioblastoma (GBM). TTFields are applied continuously using a set of four transducer arrays placed on the skin. The main TTFields-related adverse event is mild-moderate dermatitis occurring under the arrays, which is primarily caused by long-term exposure to irritants and may be exacerbated by local hyperhidrosis and occlusion. Strategies that mitigate skin irritation may improve patients' quality of life and compliance with TTFields. Four product groups (antiperspirants, moisturizing creams, antibiotics, and skin barriers) have been anecdotally reported to alleviate factors related to TTFields-related skin irritation. Nonetheless, not all of the aforementioned products are compatible with TTFields as some may increase electrical impedance, which may lead to increased temperatures beneath the arrays. This study investigated the effect of applying 40 commercially available skin care products on electrical impedance during TTFields application, using a rat model. Material and Methods: In these experiments, 200 kHz TTFields were applied using ceramic disks and hydrogels identical to those used with human arrays. Changes in impedance caused by applying each product on the rat skin were measured using the Optune device and an LCR meter system. Results: The review identified a set of skin care products from all 4 groups that did not lead to a significant change in the impedance. Preliminary tests in the clinical setting with these products were promising in a few patient case studies. Conclusion: These results suggest that local application of TTFields-compatible skin care products could maintain normal electrical resistance of the scalp-array interface, thereby allowing optimal delivery of TTFields to the brain. These products should be prospectively investigated for their potential role in minimizing TTFields-related skin irritation.